Polypropylene Plastic Cup Tensile Strength Optimization in Injection Molding from the Mold Variables Using Response Surface Methodology - Ogochukwu Chinedum Chukwunedum; Nelson Obinna Ubani; Jude Ezechi Dara (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Injection molding demands careful control of processing conditions to achieve durable plastic products. In polypropylene cup production, improper mold settings can reduce tensile strength, resulting in cracks, fractures, and product failure during handling, transportation, and use. Such defects increase material wastage and reduce manufacturing profitability. This study therefore aimed to develop an optimization model for maximizing the tensile strength of a polypropylene plastic cup using Response Surface Methodology. Injection pressure, injection speed, mold temperature, and cooling time were considered as process variables, while tensile strength served as the response variable. A Design of Experiments framework based on Response Surface Methodology was applied through iterative trial moldings with systematic variation of input parameters. Statistical evaluation using analysis of variance was conducted to determine model adequacy and factor significance. The results identified optimal settings of 95 MPa injection pressure, 50 mm/s injection speed, 57.27 °C mold temperature, and 15 s cooling time, yielding a maximum tensile strength of 31.44 MPa. The selected quadratic model was significant, with a coefficient of determination of 95.97 percent, indicating strong agreement between predicted and experimental results. Injection pressure showed the most significant effect on tensile strength, including its quadratic term. The study demonstrates that systematic parameter optimization enhances product strength, minimizes defects, and improves production efficiency and profitability in plastic cup manufacturing